Histopathological Evaluation of Ameliorated Effect of Citric Acid on Infarcted Myocardium - Hafiz Muhammad Imran Aziz, Muhammad Umar Talha, Ajmal Afzal, Binish Anwar, Namra Iqbal, Zarrin Khaliq (Pakistan Journal of Medical & Health Sciences, 2023)
The estimated disease burden of ischemic heart disease in Pakistan is in millions and discovery of cardioprotective agents of organic origin has great importance to decrease the financial burden on society. Objective: The study was designed to analyze and grade histopathological changes in experimental model of myocardial infarction. Study Design: This was an experimental randomized controlled trial. Place and Duration: The study was organized at King Edward Medical University and University of Veterinary and Animal Sciences, Lahore for a period of 180 days. Methodology: During initial 14 days, cont-group and Isopro-group were treated with 1 ml normal saline, while Citric-250 and Citric-500-group were treated with citric acid at 250 mg and 500 mg per-kg-body-weight respectively. Isoproterenol (85mg per-kg-body-weight) was injected subcutaneously for induction of acute myocardial infarction in all rabbits except for cont-group. Histopathological analysis was done, serum-C.K-M.B (creatine-kinase-M.B), serum-L.D.H (lactate-dehydrogenase) and cTn-I (cardiac.troponin-I) were recorded at the end of experiment. S.P.S.S software (statistical package for social sciences) was applied for statistically analyzed of data. Results: Isopro-group showed augmented odema, infiltration and necrosis in myocardium on histopathological study along with elevated level of C.K-M.B, L.D.H and cTn-I as compare to other group. Citric-250 and citric-500-group showed significant recovery with reduced odema, infiltration and necrosis in myocardium on histopathological analysis along with lesser values of C.K-M.B, L.D.H and cTn-I as compare to Isopro-group. Practical Implication: Consumption of citric acid protects from acute myocardial infarction. Conclusion: It is concluded that citric acid possesses strong cardioprotective potential. It reduces the myocardial injury during infarction in term of edema, infiltration and necrosis that help myocardium to survive during ischemic condition. Keywords: Citric acid, Isoproterenol, Formalin, cTn-I, Infiltration and Myocardial Infarction.